Carney complex with multiple breast tumours including breast cancer: a case report. Issue 6 (23rd June 2022) - Fujimoto, Akihiro; Sakakibara, Ayaka; Numajiri, Yoshiki; Matsuura, Kazuo; Kawasaki, Tomonori; Osaki, Akihiko; Saeki, Toshiaki
Abstract: Carney complex (CNC) is a rare multiple tumour syndrome characterized by cutaneous pigmented lesions, myxoma and endocrine tumours, among others, and is inherited as an autosomal dominant trait. Protein kinase cAMP-dependent type I regulatory subunit alpha ( PRKAR1A ) is known to be the responsible gene. Breast myxomatosis and ductal adenoma, which are regarded as benign, are well-known mammary lesions of CNC and are included in the main diagnostic criteria. In this case, a 59-year-old woman with repeated cardiac myxoma was diagnosed with CNC with PRKAR1A mutation. She also had three multiple breast tumours bilaterally: breast cancer, adenomyoepithelioma and intraductal papilloma. In mammary lesions of CNC, attention should be paid to benign lesions, such as breast myxomatosis or ductal adenomas, and the development of breast cancer or breast tumours with malignant potential. Mammary lesions should be aggressively scrutinized and considered for resection, as required.